PENGARUH AKUNTANSI DIGITAL, LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KINERJA UMKM DI KOTA JAMBI - Sevia Pasaribu; Fitrini Mansur; Misni Erwati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of digital-based accounting, financial literacy, and financial inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Jambi City. The challenges faced by MSME actors, such as the low utilization of digital accounting, limited financial literacy, and difficulties in accessing capital, significantly affect their performance. The research employs a quantitative approach, collecting data through questionnaires using a Likert scale. The obtained data were analyzed using SPSS version 26. The results indicate that digital accounting, financial literacy, and financial inclusion have a significant impact on the performance of MSMEs in Jambi City.